Marked Subchondral Bandlike Osteopenia on Radiography after Trauma and Inactivity: A Report of four Cases - J. Gossner; B. W. Raab; J. Larsen; S. Breitkreuz (Case Reports in Orthopedics)
We report about four cases of marked subchondral osteopenia on followup radiography after trauma and prolonged disuse. This localized form of disuse osteopenia has not been reported in details beside the followup imaging of talar neck fractures, where it is known as the “Hawkins sign.” Due to its unique morphology, it can be easily recognized as a benign finding in posttraumatic followup imaging and can be morphologically distinguished from severe complications like complex regional pain syndrome type 1 (Sudeck's disease) or periarticular osteopenia in infectious arthritis. It is important for the radiologist and orthopaedic surgeon to be aware of this form of disuse osteopenia in the proper clinical context.